2006
DOI: 10.1016/j.jpsychores.2006.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences and quality of life in atrial fibrillation: The mediating role of depression

Abstract: Objective: This study investigated gender differences, depression, and health-related quality of life (QoL) in a crosssectional sample of patients with atrial fibrillation (AF). Methods: This cross-sectional study involved a convenience sample of AF patients from two tertiary-care clinics in Toronto, Canada. Ninety-three AF patients completed psychometrically validated measures of generic QoL and depression. Mediation analyses evaluated the relationship between gender and QoL using depression as mediating vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
55
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 39 publications
17
55
1
2
Order By: Relevance
“…There are data to suggest that in the general population and among non-dialysis patients with chronic conditions and after major trauma, women also face higher prevalence of depression and poorer HRQOL [14,15,16,17]. There is also evidence that, among non-dialysis patients, depression plays a role in explaining the poorer HRQOL in women than in men [18,19]. Frustrations with unattended expectations and lack of social support are some of suggested potential explanations for a higher likelihood of depression and poorer HRQOL among women than among men [20,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…There are data to suggest that in the general population and among non-dialysis patients with chronic conditions and after major trauma, women also face higher prevalence of depression and poorer HRQOL [14,15,16,17]. There is also evidence that, among non-dialysis patients, depression plays a role in explaining the poorer HRQOL in women than in men [18,19]. Frustrations with unattended expectations and lack of social support are some of suggested potential explanations for a higher likelihood of depression and poorer HRQOL among women than among men [20,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…806,1046,1047,1048,1049 However, the rate of referral of women for catheter ablation of AF is significantly lower than men, and women are referred much later after failing more AADs. 920 There has not been consistent evidence to support female sex as a predictor of recurrence after AF ablation, based on multiple univariate and multivariate analyses.…”
Section: Outcomes Of Af Ablation In Populations Not Well Represented mentioning
confidence: 99%
“…Previous studies on heart diseases have shown that assumptions that male and female patients can be diagnosed and treated similarly -often based on research on men -has had negative consequences for women (Low, Thurston, and Matthews 2010). Regarding AF, research has demonstrated more severe clinical effects for women, including a higher mortality rate, bleeding complications (Michelena et al 2010), risk of stroke (Sullivan et al 2012;Michelena et al 2010), recurrences and higher heart rates (Volgman et al 2009) and depression-like conditions (Ong et al 2006). Consequently, attention has increased for biological sex differences and thus might be reason to suspect gender differences in communication regarding AF on the part of physicians and nurses.…”
Section: Methodsmentioning
confidence: 99%
“…Although the effects of AF tend to be worse for women (Michelena et al 2010;Sullivan et al 2012;Volgman et al 2009;Ong et al 2006), downplaying the symptoms or the health conditions for male patients may increase the risks for negligence and substandard care for these patients. Furthermore, overstating and, in some cases, almost forcing troublesome symptoms and effects onto female patients, may result in both unwarranted and inaccurate treatments, which may lead to necessary treatments being ignored (Michelena et al 2010).…”
Section: Communication As a Reproductive Actionmentioning
confidence: 99%